Metode Pengenalan Konsep dan Peran Gender (PENERANG) melalui Video dan Poster sebagai Upaya Pencegahan Kekerasan Seksual pada Anak Usia Dini - Eka Sufartianinsih Jafar; Nurazizah Aprilia Firsa; Nur Yasmin Zahra Syafiyah; Nur Afiliya Triasty Zugito; Nur Ainunnisa; Nur Fakhirah Mirsyah (AIJER: Algazali International Journal Of Educational Research, 2023)
Abstract: Methods of Recognizing Gender Concepts and Roles (Penerang) through Videos and Posters as an Effort to Prevent Sexual Violence in Early Childhood. Basically, parents want the best for their children, one of which is the desire for children to grow and develop according to their expectations and be able to carry out roles according to their gender. This study aims to introduce gender concepts and roles in early childhood (PAUD) at Az- Zehan Kindergarten. The implementation of activities is carried out using the direct observation method. The stages of implementation consist of analyzing children's needs, preparation, implementation (initial evaluation, material provision and final evaluation). The results showed that in the initial evaluation there were still 7 students who needed teacher assistance to recognize their gender concept. After being given material and explanations, all students were able to recognize their self-concept even though there were some who were still hesitant.